Care4Value: a clinical instrument data collection platform for long-term healthcare units - Ferreira, Pedro H. (2019)
The rise in healthcare costs is a major concern nowadays, especially for chronic diseases scenarios as the ones experienced in long-term healthcare units. Thus, arranging for a platform that helps these healthcare units to monitor and visualize the costs and eventual life quality gains on a per patient basis is essential. Care4Value aims to help in one of the most challenging tasks of healthcare professionals that is related to the optimization of the process of collecting and recording clinical instruments’ data. In the long run, the outcomes should allow for a predictive measurement of costs per patient, based on their clinical condition. The Care4Value ecosystem is the chief responsible for centralizing the collected data and making it available through a dashboard to the stakeholders. The data is collected by the healthcare professionals that use a mobile application and through an import module that consumes data from existing clinical systems.